Jemblung Murtadho: Packaging Islamic Da'wah Through Folk Art Performances (International Journal of Environmental Sciences, 2025)
Jemblung Murtadho is a folk art that has the function of Moslem da’wah with a traditional performance package that uses wayang media and Sholawat music. Murtadho is a master dalang who has influenced the development of Jemblung art in Blitar and its surroundings. He has a distinctive aesthetic style in presenting stories in Jemblung art. This research explores the context of the packaging of da’wah art by the dalang Murtadho in Jemblung art in Blitar, East Java. This research uses descriptive qualitative methods. Data collection used was observation, interviews, and document study. The analysis uses descriptive analysis methods. The results of the research show that the packaging of da'wah art by Jemblung Murtadho has an influence on other groups and dalang(s) in the aesthetic aspect of the style of conveying stories and da’wah in the presentation of Jemblung art performances that are developing in Blitar and its surroundings. The packaging is (1) The structure of the Jemblung performance, (2) Aesthetic humor in the Jemblung da’wah stories, (3) Presentation of Islamic songs in the performance. The packaging developed by the dalang Jemblung can be a strategy for the survival of the art of Islamic da’wah through the folk art of Jemblung Murtadho amidst the current developments in the modern world.